Enhancing Children's Competence in Religious Roles: The Development of Imams, Khatibs, and Preachers in Jorong Baduih, Tanah Datar - Fadhilatul Khaira; Arina Ilfa Rusyda; Asrianti Resita Sari; Azra Sastya Johanda; Rania Amallya; Khalis Alfarizi; Nofrita Agustia; Siti Yohana; Nafa Dwi Apriliani; Irvan Putra Pratama; Zalnofri Zalnofri; Imam Maulana; Afdhal Afdhal (Mangabdi: Journal of Community Engagement in Religion, Social, and Humanities, 2024)
This article explores the implementation of a children's leadership development program in Jorong Baduih, Tanah Datar, aimed at fostering young religious leaders to serve as imams, khatibs, and preachers. The program addresses the declining involvement of youth in religious activities due to migration and the absence of structured mentorship, which threatens the continuity of local Islamic traditions. Using a Participatory Action Research (PAR) approach, the initiative involved community leaders, religious figures, and families in identifying needs, designing training modules, and evaluating progress. The program featured hands-on training sessions, simulations, and mentorship by local religious leaders to enhance the participants' competence and confidence. The results demonstrated significant improvements in the children's ability to lead prayers, deliver sermons, and engage in public speaking, fostering a sense of responsibility and pride. Despite challenges such as limited training duration and facilities, adaptive measures ensured the program's success and highlighted the importance of community collaboration. The initiative not only revitalized religious engagement among youth but also strengthened community bonds and intergenerational cooperation. The program's sustainability is expected to be achieved through continuous community involvement and the institutionalization of regular training. This model offers a replicable framework for other communities seeking to preserve religious leadership and nurture future generations, reinforcing the value of grassroots initiatives in sustaining local religious and social development